70th birthday concert [videorecording (DVD)] - Mayall, John; Clapton, Eric; Barber, Chris, 1930-2021-; Taylor, Mick (Eagle Rock Entertainment, 2003)
It's a warm summer Saturday, July 19, 2003 in Liverpool England and the eager audience patiently waits. This concert is in celebration of John Mayall's 70th birthday and for the benefit of UNICEF's fight against child exploitation. Includes Bonus CD.